Pengaruh Pelatihan Berbasis Teori Vygotsky Terhadap Kompetensi Guru Sebagai Pembimbing (ILIN Institute Makassar, 2020)
The purpose of training based on Vygotsky's theory is that teacher’s are expected to be able to provide scaffolding in the Zone of Proximal Development (ZPD) on children’s learning, and implementation learning based on guidance in the classroom in role playing settings according to the characteristics and development of children’s learning. This research uses descriptive analysis method with a quantitative approach. The type of research used was a quasi experiment. The result this research with T test showed a value of significance smaller than the level of 5% (0.006<0.05) and the coefficient of determination (R2) shows of 87.2%. Teacher’s competency as a guide in kindergarten has increased scores. Pedagogic competence with score 87,5 (good category), personal with score 87,9 (good category), social with score 50 (good enough), and professional with score 97,2 (very good). The conclusion of this reseach is that training based on Vygotsky's theory has a significant effect on the competence of teacher’s as counselors in kindergarten.